Characteristics of Patients with Eyelid Laceration in Kariadi General Hospital Semarang: Oral Presentation - Observational Study - Resident - ADERIESTA PADMASTRIMAYA; RAJA ERINDA (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : Eyelid laceration is one of the most common ocular injuries with complications. This study examines patient characteristics with eyelid lacerations at Kariadi General Hospital Semarang. Methods : An observational study used medical records data from April 2019 to January 2023. Age, gender, eyelids, grading, area of laceration, mechanism of trauma and injury, canthal and canalicular involvement, associated injury, and surgery were recorded. Results : From 75 patients, lacerations were more common in men (56, 75%) and ages 16-<50 years (43, 57%). Lacerations occurred in right lower (21, 28%), right upper (17, 23%), right upper and lower (16, 21%), left lower (9, 12%), left upper (8, 11%), and left upper and lower (4, 5%) eyelids. They were mainly medial (52, 69%), lateral (12, 16%), and central (7, 9%). Full-thickness lacerations (58, 77%) outnumbered lamellar thickness (17, 23%). Blunt trauma (63, 84%) was the main mechanism, with motor vehicle accidents leading 30 (40%). Canthal involvement was absent in 41 cases (55%), medial in 29 (39%), and lateral in 5 (7%). Canalicular involvement was absent in 39 cases (52%) and present in 36 (48%). The three most frequent of associated injury of the patients was 16 (21%) subconjunctival bleeding, 12 (16%) orbital hematom, 9 (12%) conjunctival laceration. All patients underwent surgery, with eyelid repair most common (32, 43%). Conclusion : Eyelid lacerations mainly involved right lower eyelid, medial region, and are full-thickness. Blunt trauma, particularly motor vehicle accidents, was the main cause. Most cases lack canthal or canalicular involvement. Eyelid repair was the most frequent choice of surgery.